Safe abortion service and post abortion care: Understanding complications - Thapa, Sudha; Satyal, Indira; Malla, Kasturi (Nepal Journal of Obstetrics and Gynaecology, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Aim: To see if unsafe abortions are getting lesser after the establishment of comprehensive abortion care (CAC) Unit since March 2004. Methods: Retrospective study of women admitted with complication of abortions [induced (medically/criminal) or spontaneous] during the entire ten years period after the inception of post abortion care (PAC) Unit 2095 May -2007 April; the last 3 years overlapping the service years of CAC Unit establishment. Result: CAC and PAC units both are using manual vacuum aspiration (MVA) to procure uterine evacuation. CAC clients in the last 3 years have reached to a little less than 10,000. This is close to MVA services provided in the PAC Unit in the last 10 years amounting to 11,519. But the number (n=3958) of service provided by the PAC Unit for a complete period of three years 2058-2060 (April 2001 - April 2004) showed a slight increase to (n=4323) as the CAC Unit became functional during the 2061-2063 (15th April 2004- 2007). The complications observed in PAC unit while providing MVA are much more than CAC unit (5.75%: 2%). But the nature of complication is much more serious in CAC Unit, 10 of them needing laparotomy for 20(0.02%) cases of uterine perforation. The induced abortion rate within the hospital, three years before and during CAC services is almost similar (4.07%: 4.34%). Seriousness of the problem has definitely reduced during recent 3 year's period (Baisakh 2061-2063 Chaitra) i.e. 52: 34 except for an unfortunate rise in uterine perforation from 8 to 29 cases, 10 being from the CAC Unit. Conclusion: Though the number of complicated cases of induced abortion seeking hospitalization has not changed much after inception of CAC services in the recent three years, there is definitely a decline in the admission of more serious complicated cases of induced abortion in the recent years with unfortunate rise in number of cases of uterine perforation. doi:10.3126/njog.v2i1.1476 N. J. Obstet. Gynaecol Vol. 2, No. 1, p. 44 - 49 May -June 2007